2012
DOI: 10.1111/cge.12021
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and clinical presentation of HKαα and anti‐HKαα alleles in southern Chinese subjects

Abstract: The HKαα allele is a rearrangement occurring in the α-globin gene cluster containing both the -α(3.7) and ααα(anti4.2) unequal crossover junctions. The anti-HKαα allele is the reciprocal product containing both the -α(4.2) and ααα(anti3.7) unequal crossover junctions, which had been predicted but had not been detected previously. The phenotypic feature and population frequency of these two unusual alleles were not described. We report the identification of nine individuals carrying the HKαα allele and two indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 16 publications
4
20
0
Order By: Relevance
“…This supposition was confirmed by our findings. As with the --SEA allele, the adult individuals with the HKaa/--SEA genotype presented with a typical a-thal trait phenotype, similar to those previously reported (5,14). This will provide some clinical implications in the regions with different types of deletional a-thal (15).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…This supposition was confirmed by our findings. As with the --SEA allele, the adult individuals with the HKaa/--SEA genotype presented with a typical a-thal trait phenotype, similar to those previously reported (5,14). This will provide some clinical implications in the regions with different types of deletional a-thal (15).…”
Section: Discussionsupporting
confidence: 75%
“…In a recent study, the HKaa carrier rate was reported to be 0.07% in the Guangxi Zhuang Autonomous Region, a southern province of China (5). In daily practice, simple HKaa carriers could be mistaken for -a 3.7 allele carriers, as the individuals described in this study.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…MLPA can also discriminate between heterozygote and homozygote triplication. For samples with either an aaa anti3.7 or aaa anti4.2 junction, the tworound nested PCR strategies were also used to detect the HKaa or anti-HKaa allele according to previous studies [8,9].…”
mentioning
confidence: 99%
“…It consists of an intact a2-gene and an a1/a2 fusion gene (-a 3.7 ) with neither decreased nor enhanced agene dosage. In a recent study, the HKaa carrier rate was reported to be 0.07% in the Guangxi Zhuang Autonomous Region, a southern province of China (10). As our routine gap-PCR assay for a-thalassemia mainly targets on -SEA , -a 3.7 , and -a 4.2 deletions, but not triplicated a-genes (e.g., aaa anti4.2 and aaa anti3.7 ), simple HKaa carriers would be mistaken for -a 3.7 allele.…”
Section: Discussionmentioning
confidence: 99%